PV Smart Grid Monitoring System Based on Hybrid Telepot and Web Server - Eka Maulana Maulana; Ramadhani Kurniawan Subroto; Lunde Ardhenta (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Monitoring system in the smart grid is a key aspect that determines the reliability of transmission and communication systems in the power grid. The aim of this research is to conduct monitoring in smart grid easier and obiquitous remotely. Measured electrical parameters in smart gird are monitored through Telegram social media and webservice internet-based wirelessly. The role of web service and telepot in the smart grid monitoring system are installed in Raspberry Pi 3 which responsible to receive and process data from sensor module on each nodes and saved in database. The MySQL database accommodates amounts of data containing information on the value of current, voltage, power and time stamp which deliver by sensor node. Web programming is designed using PHP to generate connection to the database and node sensor status that runs continuously. Processed data are conducted in telepot and it is converted in to *.csv file type before sent to the telegram user. The information were also shown in web site as well as in telegram over graph display form that utilize the Highcharts library. Graphs that shows information on voltage, current, and power values can be accessed through a browser using IP address from the Raspberry Pi 3 server. When the users request information to the server, they only need certain command through Telegram social media or open the web broser to access the information from the smart grid system.